Striving for sustainable value chain establishment: a multiple feasibility analysis approach - Herman, M. I.; Minh, Thai Thi (Emerald Publishing Limited, 2021)
Purpose – Over the last decade, value chain for development has shown its bias towards global value chain approaches. This article proposes a holistic framework to carry out feasibility analysis for the establishment of a value chain.